Bank Wakaf Mikro: Its Operations and Its Role in Empowering Communities Surrounding Islamic Boarding Schools in Indonesia - Rozalinda Rozalinda; Nurhasnah Nurhasnah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This study aims to examine the operation of BWMs (Bank Wakaf Mikro, or Micro Wakaf Bank) in Islamic boarding schools and its role in the economic empowerment of the Muslim community surrounding them. Many poor people cannot access financial services because they are seen as unbankable. BWMs were established to address this issue. This research is a type of qualitative descriptive study, conducted at BWMs in West Sumatra, Yogyakarta, Central Java and East Java. Data collection techniques are done by interview, observations and documentation data. The results show that BWM is a Sharia Microfinance Institution (LKMS) incorporated as a cooperative. The empowerment model carried out by BWM is to provide financing and assistance to poor but potentially productive market segments located around the vicinity of Islamic boarding schools. Distribution of funding follows a group pattern with a joint responsibility scheme. In its journey, BWM has shown its role in community economic empowerment through providing training to prospective customers, then channeling financing to those who pass the group feasibility test. They also provide further assistance to these customers through weekly learning circles (halaqah) activities.Penelitian ini bertujuan membedah operasional BWM di pondok pesantren dan peranya terhadap pemberdayaan ekonomi masyarakat Muslim di lingkungan sekitarnya. Banyak masyarakat miskin tidak dapat mengakses jasa keuangan karena mereka dipandang unbankable. Padahal, Bank Wakaf Mikro (BWM) didirikan untuk menjawab persoalan tersebut. Penelitian ini merupakan jenis penelitian deskriptif kualitatif, dilakukan pada BWM yang ada di Sumatera Barat, Yogyakarta, Jawa Tengah, dan Jawa Timur. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan data dokumentasi. Hasil penelitian menunjukkan bahwa BWM merupakan Lembaga Keuangan Mikro Syariah (LKMS) berbadan hukum koperasi. Model pemberdayaan yang dilakukan oleh BWM adalah menyediakan pembiayaan dan pendampingan dengan segmen pasar masyarakat miskin potensial produktif yang berada di sekitar pondok pesantren. Penyaluran pembiayaan dan pendampingan menggunakan pendekatan kelompok dengan sistem tanggung renteng. Dalam perjalannya BWM sudah menunjukkan perannya dalam pemberdayaan ekonomi masyarakat melalui pemberian pelatihan kepada calon nasabah, kemudian menyalurkan pembiayaan kepada nasabah yang lulus uji kelayakan kelompok dan memberikan pendampingan kepada nasabah yang menerima pembiayaan melalui kegiatan halaqah mingguan.